PENGEMBANGAN PENDEKATAN FONIK BERBANTUAN KARTU KATA DIGITAL SCRATCH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Ninis Andini Wafa Tufahati; Indah Nurmahanani; Jennyta Caturiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media based on a phonics approach using digital word cards assisted by the Scratch application to improve elementary school students' early reading skills. This study uses the Research and Development (RnD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. At the analysis stage, a literature review and field study were conducted to identify students' early reading needs and problems. The design stage includes the creation of media materials and flowcharts, while the development stage includes the creation of storyboards, validation by media and material experts, and revisions based on their suggestions. Implementation was carried out on grade 1 students of SDN 2 Nagrikaler through four meetings, and the evaluation stage was carried out to improve the media. The validation results showed that the media achieved a feasibility score of 78% from media experts (feasible category) and 86% from material experts (very feasible category). The normality and homogeneity tests of the pretest and posttest data showed that the data results were normally distributed and homogeneous. The t-test produced a significant value of 0.000, which indicated a significant difference in the average pretest and posttest scores. N-gain analysis shows a score of 0.6125 (moderate category) with an effectiveness of 61% (quite effective). Thus, the phonics approach assisted by Scratch digital word cards is effective in improving elementary school students' early reading skills, providing an interactive learning experience, and can be an alternative solution in early literacy learning.